2018
DOI: 10.3363/prb.34.1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of fibrous hydroxyapatite particles by homogeneous precipitation and microwave-assisted hydrothermal heating

Abstract: Preparation conditions of fibrous hydroxyapatite (Ca 10 (PO 4 ) 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The present authors also took notice of the preparation of TiO2 nanoparticles from the aqueous solution, with the prospects of the fabrication of composite materials with other functional materials in order to achieve the one-pot liquid phase synthesis. We further focused on the preparation of TiO2 nanoparticles through the homogeneous precipitation method using urea, because our previous reports [7][8] demonstrated that the homogeneous precipitation method has a special and simple technique to control the amount of the reaction-participating ligands from the urea, due to the slow hydrolysis to release ammonia in the solution. In order to meet such requirement, we selected a potassium titanium oxalate (K2TiO(C2O4)2) having the characteristic crystal structure of 'eightmembered rings of four Ti and four O atoms' as a starting material; each Ti 4+ ion having the six ligand sites forms the distorted octahedron, two of which are the μ-oxo bridging oxygen ions belonging to the eight-membered ring and four of which are occupied by two chelate-coupled oxalate groups.…”
Section: Introductionmentioning
confidence: 99%
“…The present authors also took notice of the preparation of TiO2 nanoparticles from the aqueous solution, with the prospects of the fabrication of composite materials with other functional materials in order to achieve the one-pot liquid phase synthesis. We further focused on the preparation of TiO2 nanoparticles through the homogeneous precipitation method using urea, because our previous reports [7][8] demonstrated that the homogeneous precipitation method has a special and simple technique to control the amount of the reaction-participating ligands from the urea, due to the slow hydrolysis to release ammonia in the solution. In order to meet such requirement, we selected a potassium titanium oxalate (K2TiO(C2O4)2) having the characteristic crystal structure of 'eightmembered rings of four Ti and four O atoms' as a starting material; each Ti 4+ ion having the six ligand sites forms the distorted octahedron, two of which are the μ-oxo bridging oxygen ions belonging to the eight-membered ring and four of which are occupied by two chelate-coupled oxalate groups.…”
Section: Introductionmentioning
confidence: 99%